2020
DOI: 10.1155/2020/8128717
|View full text |Cite
|
Sign up to set email alerts
|

Skin Cancer Prevalence in Outdoor Workers of Ski Resorts

Abstract: Background. Snow reflectivity and altitude increase the exposure of ski resort workers to solar ultraviolet radiation. The aim was to assess the presence of skin cancer in ski resorts workers and compare it with other groups of outdoor workers reviewing published studies. Methods. An observational cross-sectional prospective study was conducted in the three largest ski resorts in Spain: Baqueira Beret, Lleida; Formigal, Huesca and Sierra Nevada, Granada. All outdoor workers including ski instructors were invit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…Although most of our population lived in an urban environment, the BCC group worked more outdoors, and for longer, than controls. Interest in occupational UVR exposure increased over recent years, and several studies have reported a higher risk of NMSC in outdoor workers, including mountain guides, farm laborers, and ski resort workers 8,17,18 . These findings underscore the importance of promoting and supporting photoprotective behaviors and the proper use of sunscreen among outdoor workers.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although most of our population lived in an urban environment, the BCC group worked more outdoors, and for longer, than controls. Interest in occupational UVR exposure increased over recent years, and several studies have reported a higher risk of NMSC in outdoor workers, including mountain guides, farm laborers, and ski resort workers 8,17,18 . These findings underscore the importance of promoting and supporting photoprotective behaviors and the proper use of sunscreen among outdoor workers.…”
Section: Discussionmentioning
confidence: 92%
“…Data regarding age, sex, marital status, income, height, weight, place of residence (rural/urban), profession, phenotype and phototype, and chronic medication were collected. Sun exposure and photoprotection habits were evaluated using a validated questionnaire previously used by our group 7,8 ; dietary habits were evaluated using the validated PREDIMED questionnaire 9 ; exposure to pollution, toxic substances and ionizing radiation was reported by participants; perceived stress was evaluated using the Perceived Stress Scale (PSS) 10,11 ; and the number of hours of sports (outdoors and indoors) and number of hours of sleep were measured (Figure S1).…”
Section: Methodsmentioning
confidence: 99%
“…The variables collected were as follows: age, sex, marital status, income, height, weight, body mass index (BMI), place of residence (rural/urban), profession, phenotype and phototype, and chronic medication; sun exposure and photoprotection habits were evaluated using a validated questionnaire previously used by our group [7,8]; diet was evaluated using the validated PREDIMED questionnaire [9]; exposure to pollution, toxic substances, and ionizing radiation was reported by participants; stress was evaluated using the Perceived Stress Scale (PSS) [10,11]; number of hours of sport practice (outdoors and indoors) and number of hours of sleep was also recorded (Supplementary Material S1).…”
Section: Methodsmentioning
confidence: 99%
“…In the last years, there has been an increasing interest in the occupational UVR exposure and there are many articles that evidence a higher risk of keratinocyte carcinomas in outdoor workers, such as mountain guides, farm workers, or workers of ski resorts. [64][65][66] This circumstance makes it necessary to adapt the photoprotection behavior and the sunscreen used to different outdoor workers' situations.…”
Section: Outdoor Workersmentioning
confidence: 99%